ANALYSIS OF GRAMMATICAL ERRORS IN THE ESSAY WRITING OF EIGHTH-GRADE STUDENTS AT PANCA BUDI MEDAN - Lilis Handayani Napitupulu; Dwi Sepriani Girsang; Yofany Maylina Nainggolan; Ckrisnawati Sinambela; Gema Hariana Sinaga (English Language Teaching Prima Journal (ELT), 2023)
This research is aimed to analyse grammatical errors in the written essays that consists of simple present tense and simple past tense. The sample member in this research is the eighth-grade students who attend Panca Budi school Medan where simple random sampling method is adopted to generate the participants. Qualitative and descriptive research methods are used as the research design. Documentation method is used as the data collection method because the data are the descriptive essays written by 40 eighth-grade students. The research results revealed that all 4 types of errors were found in the students’ essays such as omission, addition, misinformation, and mis ordering. Omission type of errors were known to be dominating with 92 times of occurrence, followed by addition errors with 70 times of occurrence, misinformation errors with 54 times of occurrence, and lastly, mis ordering errors with only 8 times of occurrence. Therefore, eighth-grade students of Panca Budi school Medan commit a significant large number of errors. Keywords: Grammatical Errors, Surface Strategy Taxonomy, Simple Past Tense, Simple Present Tense, Eighth-grade Students.